THE EFFECT OF DEBT TO EQUITY RATIO, NET PROFIT MARGIN AND EARNING PER SHARE ON SHARE PRICES IN CHEMICAL SUBSECTOR COMPANIES IN SOUTHEAST ASIA 2012 – 2018 (Case Study of a Company Listed on the Southeast Asian Stock Exchange) - Sunaryo, Deni (Dinasti International Journal of Economics, Finance & Accounting, 2020)
This study aims to analyze the effect of Debt to Equity Ratio (DER), Net Profit Margin (NPM) and Earning Per Share (EPS) simultaneously or partially on stock prices in chemical subsector manufacturing companies listed on the Southeast Asian Stock Exchange in 2012. -2018. The population is chemical sub-sector companies listed on the Southeast Asian Stock Exchange from 2012 to 2018. The research sample was 11 companies in the chemical sub-sector obtained by using purposive sampling technique. The data collection technique uses the documentation method, while the data analysis technique uses multiple linear regression analysis which is supported by the classical assumption test, namely the normality test, multicollinearity test, heteroscedasticity test, and autocorrelation test. The results showed that partially the DER variable, EPS had a significant positive effect, and the NPM variable had a significant negative effect. Simultaneously, DER, NPM, and EPS variables have a significant effect on stock prices. The R Square value of 0.114 indicates that the DER, NPM, and EPS variables are 11.4%, while the remaining 88.6% are influenced by other variables outside the regression model.